2020
DOI: 10.1111/jch.14154
|View full text |Cite
|
Sign up to set email alerts
|

Association of thyroid hormones with blood pressure and arterial stiffness in the general population: The Dali study

Abstract: Thyroid dysfunction (hyperthyroidism and hypothyroidism) may increase the risk of hypertension. 1 Hyperthyroidism and hypothyroidism are also common among hypertensive patients, 1 and hypertension guidelines suggest the need for evaluating the thyroid functions of hypertensive patients. 2 From the perspective of preventing hypertension induced by thyroid dysfunction, early intervention should be considered. Thus, it is essential to investigate the association between thyroid function and the indicators of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…In current clinical practice, thyroid function was evaluated mainly based on the levels of TSH and thyroid hormone. Previous studies have shown that overt hyper-and hypothyroidism were wellestablished risk factors for hypertension 6,7,15 . A study performed 24-hour ambulatory blood pressure monitoring in subjects with thyroid dysfunction, and found that all the patients showed higher blood pressure than euthyroid subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In current clinical practice, thyroid function was evaluated mainly based on the levels of TSH and thyroid hormone. Previous studies have shown that overt hyper-and hypothyroidism were wellestablished risk factors for hypertension 6,7,15 . A study performed 24-hour ambulatory blood pressure monitoring in subjects with thyroid dysfunction, and found that all the patients showed higher blood pressure than euthyroid subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also detected a positive relationship between thyroid-stimulating hormone (TSH) and blood pressure in euthyroid population [9][10][11] , but others failed to obtain this result [12][13][14] . In addition, some study found a positive relationship between free thyroxine (FT4) and arterial stiffness 13,15 . However, the other came to the opposite conclusion 16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, only few studies have explored the relationship between BP and thyroid hormones in healthy subjects, in order to understand whether different levels of thyroid hormones, within a physiological range, can reflect changes in BP. In this context, in the current issue of the Journal, Jamal and colleagues offer their elegant investigation conducted on 691 healthy subjects 3 . The authors elegantly show that in a physiological context, augmented serum levels of triiodothyronine (T3) and thyroxine (T4) are associated with an increase of both peripheral and central BP.…”
Section: Figurementioning
confidence: 99%
“…In this context, in the current issue of the Journal, Jamal and colleagues offer their elegant investigation conducted on 691 healthy subjects. 3 The authors elegantly show that in a physiological context, augmented serum levels of triiodothyronine (T3) and thyroxine (T4) are associated with an increase of both peripheral and central BP. A strength of the study is denoted by the choice to measure central BP, which is suggested to be a more reliable prognostic marker in cardiovascular disorder compared to conventional brachial cuff BP.…”
mentioning
confidence: 99%
See 1 more Smart Citation